The Challenges and Opportunities for Private Schools in Kabul - Muneeb, Ataullah; Ghous, Mer Ghausuddin; Nizami, Hamdullah (Eximia, 2023)
The purpose of this study is to find out the opportunities and challenge prevail to private’s schools in the city of Kabul. Data were collected using semi structured interview. The interview is conducted with the principal and teachers of private schools in Kabul. The thematic analysis has done to obtain the results and findings of the study. In this research, opportunities and challenges such as discipline, daily study time in schools, parental involvement, course completion, socio-economic challenges of students and private schools were found to be some important factors. Classroom facilities and infrastructure are not well equipped in private schools, parental involvement, and syllabus completion were found to be less considered in the study. The challenges that are prevail to private schools are student’s misbehavior, lack of infrastructure and resources, lack of advanced technologies, strict rules and regulation by higher education of Afghanistan, lack of budgets, no support by the government, and no standardized curriculum, which are serious issues that are prevail to private schools. There are some opportunities such as eligibility to apply for different international scholarship, passing international exams, transportation, and internet facilities. Afghanistan is already plagued with different views on national and international issues due to the different curricula taught by different institutions in different schools during the war. Some of the differences found in this research are significant and may give students additional benefits.